The susceptibility of aphids, Aphis gossypii glover to lauric acid based natural pesticide - Sharifah Fathiyah, Syed Mohamad; Shahril, Mohamad; Azila, Abdul Aziz, Dr. (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.